2011
DOI: 10.1111/j.1552-6569.2011.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Imaging of In Vitro Clot Sonothrombolysis by MR‐Guided Focused Ultrasound

Abstract: T2 is the most appropriate sequence for the evaluation of mechanical MRgFUS sonothrombolysis of an in vitro clot. These findings are consistent across the oxidative states of clot up to 48 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…After sonication, the T1 signal was grossly unchanged while the T2 and T2* signal was increased. On T2-weighted images, the postsonication samples looked like serum, corresponding to the near complete hemolytic release of hemoglobin degradation products in the extracellular fluid, as seen on histology(64). T2-weighted imaging is the optimum imaging sequence for intraoperative monitoring of MRgFUS sonothrombolysis of intracranial hemorrhage.…”
Section: Mrghifu Applicationsmentioning
confidence: 95%
“…After sonication, the T1 signal was grossly unchanged while the T2 and T2* signal was increased. On T2-weighted images, the postsonication samples looked like serum, corresponding to the near complete hemolytic release of hemoglobin degradation products in the extracellular fluid, as seen on histology(64). T2-weighted imaging is the optimum imaging sequence for intraoperative monitoring of MRgFUS sonothrombolysis of intracranial hemorrhage.…”
Section: Mrghifu Applicationsmentioning
confidence: 95%
“…It can facilitate a highly controlled sonothrombolysis to remove ICH and IVH clots with extreme precision under real‐time MRI observation followed by clot removal using twist‐drill craniostomy and aspiration tube . Clot lysis is confirmed by increased T2‐weighted signal changes on intraoperative MRI providing the ability to decide when to stop and carry out aspiration of the lysate . Contrary to the present catheter‐based approaches in which the catheter needs to be placed along the long axis of the clot for maximal dissolution, the shape of clot does not cause any concern with MRgHIFU and the procedure can be easily repeated if required due to its minimal‐invasiveness.…”
Section: In‐vivo Hifu Studiesmentioning
confidence: 99%
“…87 Clot lysis is confirmed by increased T2-weighted signal changes on intraoperative MRI providing the ability to decide when to stop and carry out aspiration of the lysate. 88 Contrary to the present catheter-based approaches in which the catheter needs to be placed along the long axis of the clot for maximal dissolution, the shape of clot does not cause any concern with MRgHIFU and the procedure can be easily repeated if required due to its minimalinvasiveness. With the just simple adjustment of parameters on the computer software, an HIFU lesion can be made in the septum pellucidum of casted ventricle to augment CSF circulation between the lateral ventricles, boost dissolution of blood clot, and improve hydrocephalus thereby allowing for a multimodal treatment of ICH and IVH without even moving the patient or the transducer.…”
Section: Hemorrhagic Strokementioning
confidence: 99%
“…This method exhibited good sensitivity but relatively low specificity in predicting the occurrence of HT (18). Previously, related studies have been completed and these have revealed that while a patient may exhibit retention of contrast at multiple sites, the outcomes at each site may be different, suggesting that this method may not be suitable for application to the clinical setting (19). Furthermore, this technique is utilized following arterial thrombolysis, which precludes its application in therapy decision and in patients undergoing intravenous thrombolysis.…”
Section: Applications and Development Of Permeability Imaging In Ischmentioning
confidence: 99%
“…Furthermore, this technique is utilized following arterial thrombolysis, which precludes its application in therapy decision and in patients undergoing intravenous thrombolysis. However, it has been indicated that the aforementioned phenomena is associated with the disruption of the BBB and HT (19). A previous study demonstrated that HT induced by ischemic stroke starts from the microvasculature (20), and the BBB defect is a key step during HT.…”
Section: Applications and Development Of Permeability Imaging In Ischmentioning
confidence: 99%